Impact of prosthesis–patient mismatch on mitral regurgitation after aortic valve replacement. Issue 20 (11th October 2010) - Unger, P; Magne, J; Eynden, F Vanden; Plein, D; Van Camp, G; Pasquet, A; Cosyns, B; Dedobbeleer, C; Lancellotti, P
Abstract : Background: Mitral regurgitation is frequently observed in patients undergoing aortic valve replacement (AVR) for aortic stenosis and often improves postoperatively, mainly due to left ventricular remodelling and changes in loading conditions. Aortic prosthesis–patient mismatch (PPM) is associated with poor outcome and lesser left ventricular remodelling. This study tested the hypothesis that aortic PPM affects mitral regurgitation. Methods and results: Echocardiography was performed preoperatively and before discharge in 42 patients with aortic stenosis undergoing isolated AVR and presenting mitral regurgitation with an effective regurgitant orifice (ERO) of 10 mm 2 or greater, as assessed by the proximal isovelocity surface area method. Postoperatively, mitral ERO and the regurgitant volume decreased from 16±5 mm 2 to 12±6 mm 2 (p<0.001) and from 28±8 ml to 16±9 ml (p<0.0001), respectively. PPM (indexed effective prosthetic valve area (EOAi) ≤0.85 cm 2 /m 2 ), present in 23 patients (55%), was associated with a smaller decrease in regurgitant volume (p=0.0025) and ERO (p=0.02). A functional aetiology of mitral regurgitation was associated with a larger improvement in mitral regurgitation. In the whole cohort, EOAi correlated with the changes in mitral regurgitation severity (ERO r=0.44, p=0.01; regurgitant volume r=0.47, p=0.003). However, these relationships were no longer significant in the subset of patients with functional mitral regurgitation in whom mitral regurgitation changes were mainly related to postoperative changes in mitral valve deformation. Conclusions: The presence of PPM after AVR attenuates postoperative mitral regurgitation changes, mainly in patients with organic mitral regurgitation.